2012
DOI: 10.1103/physreva.85.011606
|View full text |Cite
|
Sign up to set email alerts
|

Evolution from BCS to BEC superfluidity in the presence of spin-orbit coupling

Abstract: We discuss the evolution from BCS to BEC superfluids in the presence of spin-orbit coupling, and show that this evolution is just a crossover in the balanced case. The dependence of several thermodynamic properties, such as the chemical potential, order parameter, pressure, entropy, isothermal compressibility and spin susceptibility tensor on the spin-orbit coupling and interaction parameter at low temperatures are analyzed. We studied both the case of equal Rashba and Dresselhaus (ERD) and the Rashba-only (RO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
107
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(112 citation statements)
references
References 38 publications
5
107
0
Order By: Relevance
“…The successful realization of SOC in both Bose-Einstein condensate (BEC) [4,5] and Fermi gas [6,7] opens up a new avenue towards studying the rich physics of spin-orbit (SO) coupled ultracold atoms [8][9][10][11][12][13]. One of the important advances is that SOC was shown to have fundamental effects on the superfluidity of 3D [14][15][16][17][18][19] and 2D [19,20] continuous Fermi gases.On the other hand, the attractive Fermi gas subjected to an optical lattice [21,22] has made it possible to simulate the negative-U Hubbard model, a basic model for the superconductivity of many solid state materials [23]. In particular, the on-site attractions can induce deep bound states, which cause the conventional BCS-BEC crossover.…”
mentioning
confidence: 99%
“…The successful realization of SOC in both Bose-Einstein condensate (BEC) [4,5] and Fermi gas [6,7] opens up a new avenue towards studying the rich physics of spin-orbit (SO) coupled ultracold atoms [8][9][10][11][12][13]. One of the important advances is that SOC was shown to have fundamental effects on the superfluidity of 3D [14][15][16][17][18][19] and 2D [19,20] continuous Fermi gases.On the other hand, the attractive Fermi gas subjected to an optical lattice [21,22] has made it possible to simulate the negative-U Hubbard model, a basic model for the superconductivity of many solid state materials [23]. In particular, the on-site attractions can induce deep bound states, which cause the conventional BCS-BEC crossover.…”
mentioning
confidence: 99%
“…In addition, these recent works on thermodynamic systems showed that, unlike the α = 0 limit where the unpolarized superfluid phase is gapped and polarized superfluid phase is gapless, α = 0 allows the possibility of having a gapped polarized superfluid phase up to a critical polarization, depending on the particular value of α [14][15][16][17][18][19]. Therefore, when α = 0, in contrast to the topologically trivial unpolarized and low-polarized superfluid phases, the polarized superfluid phase with sufficiently high polarization becomes topologically nontrivial, and has gapless quasiparticle/quasihole excitations.…”
Section: B Population-imbalanced Fermi Gasesmentioning
confidence: 99%
“…On the other hand, for population-imbalanced uniform systems, the BCS-BEC evolution is not a crossover, and quantum phase transitions are found between thermodynamically stable and topologically distinct gapped and gapless superfluid phases. These phases are distinguished in momentum space by their numbers of zero-energy points, rings or surfaces (depending on the type of spin-orbit coupling) in their quasiparticle/quasihole excitation spectrum [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental realization of spin-orbit coupling (SOC) in ultracold atoms [1][2][3] has initiated substantial theoretical efforts to study its effects in 2D and 3D Fermi gases [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . This is because SOC systems with a Zeeman field, which breaks the population balance, can lead to novel types of exotic superfluid phases that may support Majorana fermions.…”
Section: Introductionmentioning
confidence: 99%